ANALISA FAKTOR-FAKTOR PENYEBAB TERJADINYA KETERLAMBATAN TINDAKAN OPERASI (DELAY TO OPERATION) DI INSTALASI RAWAT DARURAT RSUP SANGLAH DESEMBER 2017 – FEBRUARI 2018 - A, Rusdi; Sjaaf, Amal Chalik (UI Scholars Hub, 2023)
Surgery service is one of the health services in a hospital that can describe the quality of the hospital. Sanglah Hospital, Denpasar is a hospital at the provincial level which has a long waiting time for surgery. The long waiting time for surgery is generally related to factors such as the availability of facilities and infrastructure, human resources, and the length of time for approval from patients and families for surgery. Research is needed to determine the factors that significantly form the basis for determining policies at the Sanglah General Hospital level, especially in the Emergency Room, to improve operating services. observational approach and cross-sectional analysis design. This study involved 54 respondents in quantitative research and 7 informants in qualitative research. The result showed bed block events is 38,9 % from December 2017 to February 2018. Agreement following informed consent is obtained in ≥ 1 hour for 17 respondents (31,5%) and < 1 hour for 37 respondents (68,5%). Tools and equipment are complete and available in 94,4% cases and incomplete in 5,6% cases. Time consumed waiting for operation is categorized delay if ≥ 5 hours in 33,3% cases, categorized not delay if < 5 hours in 66,7%. Bivariate analysis using Chi Square showed p-value 0,000 for correlation between bed block and delay to operation, p-value 0,000 for correlation between time consumed to obtain agreement for surgery, p-value 0,012 for correlation between tools and equipment with delay to operation. The most influencing factor is operation agreement with p-value 0,005 using logistic regression. From this study, we conclude there is significant correlation between bed block, time consumed for obtain operation agreement, tools and equipment availability with delay to operation. This result is a base in making strategy to improve quality of surgery services in emergency department.